MODEL DEMOKRASI DALAM PENINGKATAN KUALITAS PELAYANAN PUBLIK (STUDI OTONOMI DAERAH DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT PASCA REFORMASI) - Yusnani Hasjimzum (Jurnal Dinamika Hukum, 2014)
Quality improvement on public service has been regulated by various regulations. Until present, there are still many complaints due to poor service provided by government which does not meet people’s expectation. Moreover, bureaucracy is still not effective to provide appropriate service to public resulting in a low quality service. To meet public’s need, people are necessarily involved in as the implementation of democracy as the effort of establishing a democratic government.Key words: democracy model, quality improvement, public service